PENGARUH NET PROFIT MARGIN (NPM), TOTAL ASSET TURNOVER (TATO) DAN CURRENT RATIO (CR) TERHADAP RETURN ON ASSETS (ROA) PERUSAHAAN SUB SEKTOR TELEKOMUNIKASI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2020 - Yudi Mulyana; Elis Badariah; Imat Hikmat; Fitria Haquei (DESANTA (Indonesian of Interdisciplinary Journal), 2023)
This research was conducted on telecommunications sub-sector companies listed on the Indonesia Stock Exchange. The purpose of this study is to find out the significant effect of the variables net profit margin, total asset turnover, and current ratio partially and simultaneously on return on assets. The population in this study amounted to six telecommunication sub-sector companies listed on the Indonesia Stock Exchange, using the purposive sampling technique. Finally, three companies were taken as samples. In this study, secondary data is used in the form of financial statements for the first quarter of 2016 to the fourth quarter of 2020 by testing the hypothesis using multiple linear regression. The results of the partial study (T-test) show that the net profit margin variable has a value of Sig. 0.000 < 0.05 and the value of t count > t table (12.841 > 2.003) and the total asset turnover has Sig. 0.000 < 0.05 and the value of t count > t table (4.569 > 2.003) has a significant positive effect on return on assets. While the current ratio has Sig. 0.858 < 0.05 and the value of t count > t table (-0.180 < 2.003) has no effect on return on assets. Then, the results of simultaneous research (F test) have a calculated F count and an F table (72.421 > 2.769), and the significance value (0.000 < 0.005) shows that the net profit margin, total asset turnover, and current ratio together affect the return on assets in telecommunications sub-sector companies listed on the Indonesia Stock Exchange for the 2016-2020 period.